Going Global through Social Sciences and Humanities: A Systems and ICT Perspective Proceedings of the 2nd International Conference "Going Global through Social Sciences and Humanities", 27-28 February 2019, Tomsk, Russia - Anikina, Zhanna (Advances in Intelligent Systems and Computing, 2019)
This book presents contributions submitted to the 2nd international conference Going Global through Social Sciences and Humanities (GGSSH 2019) held in Tomsk, Russia on 27-28 February 2019. The conference focused on such issues as interdisciplinary pedagogy, language teaching and learning, cultural studies and linguistics, particularly highlighting global academic integration and professional development for research. As such, the event provided a platform for discussions and sharing publication activities, to help Russian academics to take first steps toward global research. Showcasing the ongoing Russian research in focus areas, this book is of interest to a diverse academic audience working in social sciences and humanities, particularly those from the post-Soviet countries.